Immunological and Pathological Landscape of Dengue Serotypes 1-4 Infections in Immune-Competent Mice - Rathore, Abhay P. S.; Mantri, Chinmay K.; Tan, Meredith W.; Shirazi, Roksana; Nishida, Andrew; Aman, Siti A. B.; Morrison, Juliet; St. John, Ashley L. (Frontiers in Immunology, 2021)
Dengue virus (DENV), a Flavivirus, causes a broad spectrum of disease in humans with key clinical signs including thrombocytopenia, vascular leakage and hemorrhaging. A major obstacle to understanding DENV immunity has been the lack of a validated immune-competent mouse model. Here, we report the infection profiles of human clinical isolates of DENV serotypes 1-4 in an immune-competent mouse model. We detected replicating DENV in the peritoneal cells, liver and the spleen that was generally resolved within 2 weeks. The DENV target cell types for infection were monocytes/macrophages, dendritic cells, endothelial cells, and we identified a novel DENV cellular target, fibroblast reticular cells of the spleen. We observed gross pathologies in the spleen and liver that are consistent with dengue disease, including hemorrhaging as well as transcriptional patterns suggesting that antiviral responses and tissue damage were induced. Key clinical blood parameters that define human DENV disease such as hemoconcentration, leukopenia and reduced number of platelets were also observed. Thus, immune-competent mice sustain replicating infection and experience signs, such as hemorrhaging, that define DENV disease in humans. This study thoroughly characterizes DENV1-4 infection in immune-competent mice and confirms the wild-type mouse model as a valid and reproducible system for investigating the mechanisms of DENV pathogenesis.